A Way Forward: Nurturing the Imagination at the Intersection of Race, Class, Gender, and Age - Lockhart-Gilroy, Annie A. (Religious education, 2016)
Those who are oppressed often find themselves internalizing voices that limit their ability. This article focuses on a population that falls on the non-hegemonic side of the intersection of race, class, gender, and age: Black girls from poor and working-class backgrounds. From my work with youth, I have noticed that internalizing these limiting voices lead to a sense of personal hopelessness. I suggest that Christian educators combat personal hopelessness by nurturing the theological imagination of their youth.